2016
DOI: 10.1155/2016/9104792
|View full text |Cite
|
Sign up to set email alerts
|

A High Protein Diet Has No Harmful Effects: A One-Year Crossover Study in Resistance-Trained Males

Abstract: The purpose of this investigation was to determine the effects of a high protein diet over a one-year period. Fourteen healthy resistance-trained men completed the study (mean ± SD; age 26.3 ± 3.9 yr; height 178.5 ± 8.4 cm; and average years of training 8.9 ± 3.4 yr). In a randomized crossover design, subjects consumed their habitual or normal diet for 2 months and 4 months and alternated that with a higher protein diet (>3 g/kg/d) for 2 months and 4 months. Thus, on average, each subject was on their normal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(73 citation statements)
references
References 17 publications
2
53
1
4
Order By: Relevance
“…On each occasion, participants were given detailed written and verbal instructions on completing the food logs. Dietary intake data were analyzed using the open-sourced software myfitnesspal (MyFitnessPal, Inc., San Francisco, CA, USA), which has been employed to analyze food intake data in other studies [ 42 , 43 , 44 , 45 , 46 , 47 , 48 ].…”
Section: Methodsmentioning
confidence: 99%
“…On each occasion, participants were given detailed written and verbal instructions on completing the food logs. Dietary intake data were analyzed using the open-sourced software myfitnesspal (MyFitnessPal, Inc., San Francisco, CA, USA), which has been employed to analyze food intake data in other studies [ 42 , 43 , 44 , 45 , 46 , 47 , 48 ].…”
Section: Methodsmentioning
confidence: 99%
“…Common concerns regarding the consumption of high-protein diets are the effects of elevated protein on kidney function and bone health, and the lack of scientific evidence to support these claims has been discussed in more detail in the following review articles (Phillips, 2017;Phillips et al, 2016). Put briefly, consumption of higher protein diets does not have detrimental effects on health, including kidney function (Longland et al, 2016), bone health (Shams-White et al, 2017), or liver function and blood lipids (Antonio et al, 2016a(Antonio et al, , 2016b.…”
Section: Influence Of Higher Protein Intakes On Healthmentioning
confidence: 99%
“…A recent paper by Møller et al [ 21 ] reported no association between ahigher protein intake and decreased kidney function in pre-diabetic older adults during a one-year intervention. In a study by Antonio et al [ 22 ], high protein intake (2.5 g/kg/day) was compared to higher intake (~3.3 g/kg/day), and it was reported that these high protein diets were not deleterious for kidney function over a one-year crossover study period. However, in the present study, protein intake did not differ between the diet groups, suggesting that not only the protein intake, but also the dietary acid load, should be considered as factors that may affect renal function.…”
Section: Discussionmentioning
confidence: 99%